Future of freedom: Illiberal democracy at home and abroad - "Zakaria, Fareed" (New Delhi, 2003)
Brave and ambitious book . . . it deserves a wide readership$1 (BThe New York Times Book Review Liberty and Democracy. The two go hand in hand in popular thinking. We believe that the answer to our problems is always more democracy. More democracy means more freedom. But does it? At a time when democracy is the one political system whose legitimacy is unquestioned, this deeply significant book points out the tension between democracy and freedom. It ranges widely through the past and the present to remind us that we can have too much of a good thing. American democracy, to many, is the model for the rest of the world. Fareed Zakaria points out that the American form of democracy is one of the least democratic in use today$1 (Bit is more democratic that ever before but also more dysfunctional. As he examines the world$1 (Bs other great democracies such as those in India and Britain, he comes up with equally arresting insights. For example, he argues that in many parts of the world, the spread of democracy has not produced a corresponding growth in liberty. From Russia to Venezuela to the Palestinian Authority, we see instead a strange creature$1 (Bthe elected autocrat. Societies, particularly in the Arab world, are trapped between repressive dictatorships and fanatical masses. Is there a way out? Calling for a restoration of the balance between liberty and democracy, Zakaria argues that by restricting our democracy we enhance our freedom. Liberal democracy has to be made effective and relevant for our times and this timely book challenges us to take a fresh look at democracy in the twenty-first century. The Future of Freedom is a New York Times bestseller and has been translated into eighteen languages.s
Keywords: Political science-Philosophy